Indirect effects of habitat loss via habitat fragmentation: A cross-taxa analysis of forest-dependent species - Puttker, Thomas (2020)
Recent studies suggest that habitat amount is the main determinant of species richness, whereas habitat fragmentation has weak and mostly positive effects. Here, we challenge these ideas using a multi-taxa database including 2230 estimates of forest-dependent species richness from 1097 sampling sites across the Brazilian Atlantic Forest biodiversity hotspot. We used a structural equation modeling approach, accounting not only for direct effects of habitat loss, but also for its indirect effects (via habitat fragmentation), on the richness of forest-dependent species. We reveal that in addition to the effects of habitat loss, habitat fragmentation has negative impacts on animal species richness at intermediate (30-60%) levels of habitat amount, and on richness of plants at high ( > 60%) levels of habitat amount, both of which are mediated by edge effects. Based on these results, we argue that dismissing habitat fragmentation as a powerful force driving species extinction in tropical forest landscapes is premature and unsafe.